LINGUISTIC ANALYSIS OF ECONOMIC ADVERTISING TEXTS IN ENGLISH - MARJONA HAMIDOVA OLIMOVNA (TADQIQOTLAR, 2025)
This research explores the linguistic features of economic advertising texts in English, focusing on the vocabulary, structure, and persuasive strategies used in commercial messages. The study aims to identify how language is tailored to attract consumers, influence purchasing decisions, and reflect economic concepts through stylistic and semantic tools. Through the analysis of selected advertising samples from global markets, the paper examines syntactic patterns, lexical choices, and rhetorical techniques. The findings highlight the importance of clear, emotionally charged, and economically loaded language in shaping consumer behavior and promoting products or services effectively.